Oral Supplementation of Houttuynia cordata Extract Reduces Viremia in PRRSV-1 Modified-Live Virus-Vaccinated Pigs in Response to the HP-PRRSV-2 Challenge - Ruansit, Wilawan; Charerntantanakul, Wasin (Frontiers in Immunology, 2022)
This study evaluated the in vitro antiviral activities and the ex vivo immunomodulatory effects of Houttuynia cordata Thunb. (HC) ethanolic extracts in response to porcine reproductive and respiratory syndrome virus (PRRSV). In addition, this study evaluated the in vivo effects of oral supplementation of HC extract on immune responses to and cross protective efficacy of PRRSV-1 modified-live virus (MLV) vaccine against highly pathogenic (HP)-PRRSV-2 challenge. In vitro experiments demonstrated that HC extracted in either 50%, 70%, or 95% ethanol (referred to as HC50, HC70, and HC95, respectively) significantly interfered with PRRSV replication in MARC-145 cells. Ex vivo experiments revealed that all HC extracts significantly enhanced mRNA expressions of type I interferon-regulated genes, type I and II interferon (IFN), and pro- and anti-inflammatory cytokines in HP-PRRSV-2-inoculated monocyte-derived macrophages. An in vivo experiment included four groups of six pigs (4-week-old; n=24). Group 1 and group 2 were vaccinated with PRRSV-1 MLV vaccine at 0 dpv (day post vaccination). Group 2 also received oral administration of HC50 extract at 0-49 dpv. Group 3 received PRRSV-1 MLV vaccine solvent at 0 dpv, while group 4 served as strict control. Group 1-3 were challenged intranasally with HP-PRRSV-2 at 28 dpv and immune-related and clinical parameters were monitored weekly until 49 dpv. Compared to group 1, group 2 demonstrated significantly increased IFN regulatory factor 3 mRNA expression of PRRSV-recalled peripheral blood mononuclear cells, and significantly reduced HP-PRRSV-2 viremia. No difference of PRRSV-specific antibody responses, rectal temperature, clinical scores, and average daily weight gain was detected. Our study reports the immunomodulatory and anti-PRRSV potentials of HC extract in PRRSV-1 MLV-vaccinated/HP-PRRSV-2 challenged pigs.